Antidepressant withdrawal – the tide is finally turning. (2020) - Hengartner, Michael P.; Davies, James; Read, John
Abstract: Withdrawal reactions when coming off antidepressants have long been neglected or minimised. It took almost two decades after the selective serotonin reuptake inhibitors (SSRIs) entered the market for the first systematic review to be published. More reviews have followed, demonstrating that the dominant and long-held view that withdrawal is mostly mild, affects only a small minority and resolves spontaneously within 1–2 weeks, was at odd with the sparse but growing evidence base. What the scientific literature reveals is in close agreement with the thousands of service user testimonies available online in large forums. It suggests that withdrawal reactions are quite common, that they may last from a few weeks to several months or even longer, and that they are often severe. These findings are now increasingly acknowledged by official professional bodies and societies.